Constructing Simple Marriage as Digital Da’wah A Content Analysis of TikTok Narratives on KUA Marriage - M. Nashoihul Ibad (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
This study aims to analyze the construction of the meaning of simple marriage in the TikTok content of young Indonesians which narrates the practice of marriage in Kantor Urusan Agama (KUA) or Office of Religious Affairs As an alternative to the culture of wedding celebrations which tend to be expensive and full of social demands. This phenomenon is important to study because TikTok is not only an entertainment space, but also a space for the production of popular da'wah messages that are close to the experiences of the younger generation. Administratively, marriage contract services at the KUA office on working days and hours are free of charge, while the implementation of marriage outside the KUA is subject to a service fee of IDR 600,000 through the PNBP mechanism. This study uses a qualitative approach with digital phenomenology methods and qualitative content analysis. Data was obtained from 25–30 TikTok content in 2024 that were purposively selected from five accounts of young Indonesians who discussed marriage at KUA, simple marriage, anti-celebration of luxury, and wedding blessings. The results of the study are expected to show that marriage in KUA is constructed as a symbol of simplicity, courage against social prestige, cost efficiency, and a form of digital da'wah that emphasizes the value of sakinah, anti-israf, and household blessings. This research contributes to the study of Islamic communication and broadcasting, especially young people's digital da'wah on social media. Penelitian ini bertujuan untuk menganalisis konstruksi makna nikah sederhana dalam konten TikTok anak muda Indonesia yang menarasikan praktik nikah di Kantor Urusan Agama (KUA) sebagai alternatif terhadap budaya hajatan pernikahan yang cenderung mahal dan sarat tuntutan sosial. Fenomena ini penting dikaji karena TikTok tidak hanya menjadi ruang hiburan, tetapi juga ruang produksi pesan dakwah populer yang dekat dengan pengalaman generasi muda. Secara administratif, layanan akad nikah di kantor KUA pada hari dan jam kerja tidak dikenakan biaya, sedangkan pelaksanaan nikah di luar KUA dikenakan biaya layanan sebesar Rp600.000 melalui mekanisme PNBP. Penelitian ini menggunakan pendekatan kualitatif dengan metode fenomenologi digital dan analisis isi kualitatif. Data diperoleh dari 25–30 konten TikTok tahun 2024 yang dipilih secara purposive dari lima akun anak muda Indonesia yang membahas nikah di KUA, nikah sederhana, anti-hajatan mewah, dan keberkahan pernikahan. Hasil penelitian diharapkan menunjukkan bahwa nikah di KUA dikonstruksi sebagai simbol kesederhanaan, keberanian melawan gengsi sosial, efisiensi biaya, dan bentuk dakwah digital yang menekankan nilai sakinah, anti-israf, serta keberkahan rumah tangga. Penelitian ini berkontribusi pada kajian komunikasi dan penyiaran Islam, khususnya dakwah digital anak muda di media sosial.